The Influence of Work Environment and Culture on Employee Performance with Motivation as an Intervening Variable - Ocfa Indah Nst; A Dewantoro Marsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze the influence of work environment, work culture, and motivation on employee performance at PT. PNM Medan Tembung. The research method employed in this study is quantitative research, with data collected through questionnaires distributed to 50 employees of PT. PNM Medan Tembung. The data were then analyzed using Smart PLS 4.0 software. The results of the analysis indicate that work culture has a significant influence on employee performance, as well as employee motivation. However, no significant relationship was found between the work environment and employee performance. Additionally, employee motivation was found to mediate the relationship between work culture and employee performance. These findings emphasize the importance of creating a positive and supportive work culture and enhancing employee motivation to improve individual and organizational performance. A supportive work environment can also influence employee motivation, making it essential for companies to create a conducive and motivating work environment. In conclusion, this research provides insights into the significance of work culture and motivation in enhancing employee performance at PT. PNM Medan Tembung. The implications of this study highlight the importance of companies paying attention to and effectively managing these factors to enhance organizational productivity and efficiency. Furthermore, this research can serve as a reference for future studies in the same field